2014
DOI: 10.1016/j.jacc.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Manifestations of Fibromuscular Dysplasia

Abstract: Fibromuscular dysplasia (FMD) involving the coronary arteries is an uncommon but important condition that can present as acute coronary syndrome, left ventricular dysfunction, or potentially sudden cardiac death. Although the classic angiographic “string of beads” that may be observed in renal artery FMD does not occur in coronary arteries, potential manifestations include spontaneous coronary artery dissection, distal tapering or long, smooth narrowing that may represent dissection, intramural hematoma, spasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
105
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 116 publications
(141 reference statements)
0
105
0
5
Order By: Relevance
“…Some studies reported that FMD has autosomal dominant trait with variable penetrance but with poorly understood underlying genetics. Patients with coronary involvement of FMD usually present with dissection of an epicardial artery or major branch, which clinically leads to acute coronary syndrome (ACS) or potential sudden cardiac death [8]. Initial ECG findings might reflect acute ischemia with ST deviation and sometimes with elevated cardiac biomarkers [3].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies reported that FMD has autosomal dominant trait with variable penetrance but with poorly understood underlying genetics. Patients with coronary involvement of FMD usually present with dissection of an epicardial artery or major branch, which clinically leads to acute coronary syndrome (ACS) or potential sudden cardiac death [8]. Initial ECG findings might reflect acute ischemia with ST deviation and sometimes with elevated cardiac biomarkers [3].…”
Section: Discussionmentioning
confidence: 99%
“…FMD should be considered in any patient without cardiac risk factors presenting with ACS or new left ventricular dysfunction, especially in middle-aged women. Symptoms depend on the arterial bed affected with FMD and this is most often hypertension if the renal artery is affected, headache, or pulsatile tinnitus if cervical vessel involvement [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations